2006
DOI: 10.1016/j.jaapos.2006.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Follow-up Eye Care After Preschool Vision Screening in the Primary Care Setting: Findings From a Pilot Study

Abstract: Timely follow-up after an abnormal preschool vision screening test is necessary for the prevention of amblyopia. A previous large community-based preschool vision screening program found that only approximately half of those children who were referred were documented to have received follow-up care. 1 No similar data are available regarding follow-up from the primary care setting. We present findings from a pilot study designed to identify barriers to follow-up care faced by families screened by pediatricians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Kemper et al found that minority and low-income families were less likely to follow up, consistent with the lower rate we found among children referred by the HD sites. 31 Fourth, the study results related to screening rates, untestability, underreferral, and failure to show for ophthalmologic examinations were suboptimal, perhaps due to incomplete acceptance of screening among staff at certain primary care sites and among some parents. Confirmatory examination and treatment are necessary following a screening failure.…”
Section: Limitationsmentioning
confidence: 95%
“…Kemper et al found that minority and low-income families were less likely to follow up, consistent with the lower rate we found among children referred by the HD sites. 31 Fourth, the study results related to screening rates, untestability, underreferral, and failure to show for ophthalmologic examinations were suboptimal, perhaps due to incomplete acceptance of screening among staff at certain primary care sites and among some parents. Confirmatory examination and treatment are necessary following a screening failure.…”
Section: Limitationsmentioning
confidence: 95%
“…For example, Alotaibi (2006) revealed that the lack of low vision specialists is one of the important reasons why Saudi society has not been aware of the significance of low vision service. Kemper, Uren, and Clark (2006) also found that the greatest barriers of preschool-aged children for compliance in follow-up eye care were a lack of knowledge about the benefits of early intervention. Furthermore, Kimel (2006) reported that parent perceptions of vision problems were significant barriers.…”
Section: Knowledge Of Eye Healthmentioning
confidence: 97%
“…A large community-based preschool vision screening program [9] found only about 50% of children referred received follow-up care. Multiple issues including lack of insurance, eye-care provider availability and parental understanding negatively impact the likelihood of compliance with referrals [12 ].…”
Section: Diagnosis Of Refractive Errorsmentioning
confidence: 99%